High nasolacrimal sac-duct junction anatomical variation – retrospective review of dacryocystography images. (2nd November 2021) - Juniat, Valerie; Lee, John; Sia, Paul; Curragh, David; Hardy, Thomas G; Selva, Dinesh
ABSTRACT: Purpose: In assessing epiphora, dacryocystography (DCG) is often performed to determine the presence of any structural anomaly of the nasolacrimal drainage apparatus. We describe an anatomical variation of the nasolacrimal duct, termed high sac-duct junction (HSDJ) morphology, that is seen on DCG, which could lead to more difficult, and possibly unsuccessful, intubation of the nasolacrimal duct (NLD). Methods: This was a multi-center, retrospective, observational case series. Seven hundred and thirty-four DCGs were included in this study, of which 45 were pediatric images. DCG images underwent a blinded review by an oculoplastic surgeon for the presence of HSDJ morphology. The direct extension of the NLD from the inferior border of the lacrimal sac is commonly regarded as a normal morphology. HSDJ was defined as NLD originating from the inferior aspect of the medial wall of the lacrimal sac. Results: HSDJ was seen in 28/689 (4.1%) adult scans and 7/45 (15.6%) pediatric scans. In total, there were 35/734 (4.8%) DCGs demonstrating lacrimal sacs with HSDJ. Conclusions: We report the prevalence of an anatomical variant of the lacrimal sac and NLD, observed on DCG, in a population of patients with epiphora, where the NLD originates from the inferior aspect of the medial wall of the lacrimal sac. Knowledge of this anatomic variant may have management implications for patients with epiphora as it may make nasolacrimal intubation more technically difficult. Further studies are needed to correlate this anatomic variation with symptoms and management outcomes.